PERLINDUNGAN INVESTOR PASAR MODAL DALAM PERSPEKTIF LEGAL, DISCLOSURE DAN DIVIDEN DI BEBERAPA NEGARA - Wahyu Manuhara Putra (Journal of Accounting and Investment, 2008)
Corporate governance gives certainty protection to shareholder and parties of creditor in investing at its company. Mechanism of corporate governance consisted of transparancy, disclosure and fairness. Corporate governance is key determinant and develope of  stock market, capital and ownership structure, dividend policy and control gain of privat. Purpose of this article is to explain protection of investor through mechanism disclosure, law and dividend in some countries. Result of some researches indicate that United States, English and Japan has high law level of protection for investor while indonesia still weakening. The disclosure  level broadness of financial information there is at United States, English and Japan. On The Contrary, Indonesia still less in disclosing its financial statements. The other result states that dividend payment policy indirectly relates to protection of investor, but influenced by law enforcement system and investment opportunitis.